TECHNOLOGICAL SKILLS DEVELOPMENT FOR COMMUNITIES TO SUPPORT AN AGING SOCIETY - Poophayang , Narasak; Poophayang , Piangkae (Journal of MCU Nakhondhat, 2023)
The purpose of this research was to study the effects of technological skill development for communities. To support the aging society by using participatory action research methodology, there were 2 phases, 10 steps, 12 participants, 5 key informants, and the target group was 35 elderly people. The research tools were questionnaires, interviews, and conversations. The data was collected and then report writing according to the research objectives. The results showed that the development of technology skills for community members to support the aging society, by training communication skills through a variety of channels, both offline and online. The total number of activities was 30 hours. The contents were using the level and language to communicate their needs, such as family communication in the community and training on the use of technology as a communication tool, such as using a mobile phone, application Line and Facebook for contact and coordination in taking care of the elderly group, family members and community leaders. In addition, the results of the design of group activities for members of various age ranges, including children, children of community members, middle - aged (40 - 50 years old), preparatory age for the elderly (50 - 60 years old) and the elderly cause learning together, especially good interaction between the multi - generational groups who have participated in activities together. As a result, the elderly was satisfied at a high level. They can be used in everyday life access to news information and can contact and coordinate quickly in case of problems that require cooperation. or assistance between groups Gain knowledge and understanding in a variety of channels Able to communicate needs and necessities in daily life with quality.